Determinants of income diversification among farm households in Thailand - Charoenkittayawut, S.; Mankeb, P.; Suwanmaneepong, S. (My University, 2023)
The research finding indicated that the age and education level of the household head, the household size, household members migrating for domestic and overseas work, the amount of household debt in the informal sector, and household members’ access to credit significantly and positively affected income diversification among farm households in Thailand. The household dependency ratio, annual household income per capita, and the household's land size were found to be significantly and negatively associated with income diversification. In contrast, the sex of the household head, the amount of household debt in the formal sector, and the location of residence were not significant factors in determining income diversification. These results indicated specific factors determining income diversification, enabling policymakers to understand household resources, conditions, and social barriers. Such understanding allowed the policymaker to enhance participation in income diversification strategies in an informed and effective way.
Keywords: Farm households; Income diversification; The Simpson index of diversity